Challenges Faced for Botulinum Toxin Injection in the Treatment of Hemifacial Spasm and Blepharospasm: Our Experience in Tribhuvan University Teaching Hospital during COVID-19 Pandemic - Rajbhandari, Reema; Yadav, Jayant Kumar; Karn, Ragesh; Ojha, Rajeev; Gajurel, Bikram (Annapurna Journal of Health Sciences, 2023)
Introduction: Hemi facial spasm (HFS) and Blepharospasm (BS) is a chronic distressing condition. Botulinum toxin (BoNT) injection is one of its treatment modality. Acquiring the injection and treating the patients overcoming the lockdown hurdles of COVID pandemic has been a major challenge. Methods: Patients who were treated at Tribhuvan University Teaching Hospital (TUTH) Outpatient Department (OPD) during the COVID pandemic in 2020 and 2021 were included in this study. Results: Out of 30 patients, 77% were female. 47% were diagnosed with BS whereas the rest with HFS. About 50% of them have had symptoms for an average of 2-5 years before receiving botulinum toxin injection. The mean Jankovic score for patients before BoNT was 2.31(SD: 0.66 range 1-4). 26 patients experienced a decrease in spasm within one week of BoNT injection and had symptomatic relief. The mean Jankovic score at week 1 was 0.63(SD: 1.09 range 1-3) and the difference was statistically significant (p<0.001). After 2 weeks of BoNT therapy, all patients experienced a decrease in spasm with symptomatic improvement. The mean Jankovic score at week 2 was 0.26(SD: 0.44 range 0-1) and the difference was statistically significant (p<0.001). In terms of side effects, 4 patients experienced paresis while 26 patients experienced no side effects. No other systemic side effects were reported. Conclusion: BoNT injection has a good outcome for HFS and BS, despite its cost and the need for frequent injection. Importing the BoNT from India during the lockdown period of COVID pandemic and patients travelling within the country were challenges that were faced by the patients and doctors to achieve the result